2020
DOI: 10.1101/2020.01.23.915900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virion-associated spermidine transmits with Rift Valley fever virus particles to maintain infectivity

Abstract: 24Viruses require host cell metabolites to productively infect, and the mechanisms by which 25 viruses usurp these molecules is diverse. One group of cellular metabolites important in virus 26 infection is the polyamines, small positively-charged molecules involved in cell cycle, translation, 27 and nucleic acid synthesis, among other cellular functions. Polyamines also support replication 28 of diverse viruses, and they are important for processes such as transcription, translation, and 29 viral protein enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We observed that the polyamines significantly reduced cellular viability at approximately 5 μM, reflecting prior descriptions of high polyamine concentrations leading to apoptosis. , Despite this reduction in viability, we observed modestly reduced viral titers (Figure B). We measured polyamines in supplemented cells and observed that supplementation with any of the three polyamines resulted in only modest changes in cell-associated polyamines (Figure B, lower), as we previously described . The reduced signal with high concentrations of spermidine and spermine likely was an artifact of reduced cellular viability at these doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the polyamines significantly reduced cellular viability at approximately 5 μM, reflecting prior descriptions of high polyamine concentrations leading to apoptosis. , Despite this reduction in viability, we observed modestly reduced viral titers (Figure B). We measured polyamines in supplemented cells and observed that supplementation with any of the three polyamines resulted in only modest changes in cell-associated polyamines (Figure B, lower), as we previously described . The reduced signal with high concentrations of spermidine and spermine likely was an artifact of reduced cellular viability at these doses.…”
Section: Resultsmentioning
confidence: 99%
“…We measured polyamines in supplemented cells and observed that supplementation with any of the three polyamines resulted in only modest changes in cell-associated polyamines (Figure 2B, lower), as we previously described. 27 The reduced signal with high concentrations of spermidine and spermine likely was an artifact of reduced cellular viability at these doses.…”
Section: Polyamine Depletion Limits Coronavirus Replicationmentioning
confidence: 99%